CLINICAL AND MORPHOLOGICAL CRITERIA OF COLITIS IN PATIENTS WITH CHRONIC ISCHEMIC DISEASE OF THE DIGESTIVE SYSTEM - Khusainova Munira Alisherovna; Islamova Kamola Akramovna; Erkinova Nafisa Yorkinovna (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Chronic violation of blood flow in the basin of the abdominal aorta and its unpaired visceral branches leads to ischemia of the abdominal organs. Chronic abdominal ischemia (CAI) is characterized by pain, functional and morphological changes in the abdominal organs. The present study was conducted in order to clarify the causes of abdominal pain syndrome in patients with CAI and the features of their development of ILC. The clinical department of gastroenterology examined 42 patients with diseases of the cardiovascular system and suspected ILC. The age of the subjects ranged from 56 to 80 years, men were 24, women were 18. Of the 42 patients we examined, 41 had arterial hypertension, 40 had coronary heart disease, 31 had CVD, and 7 had atherosclerosis of the vessels of the lower extremities. Myocardial infarction was previously suffered by 8 people, stroke — 5, CABG — 1 patient, abdominal aortic prosthetics — 2 patients, 1 patient had an abdominal aortic aneurysm. According to our data, ischemic intestinal lesion ranks third among other forms of CAI. The present study has also confirmed this position. All 42 patients suffering from cardiovascular diseases with atherosclerotic vascular lesions and impaired metabolism of fats and carbohydrates had clinical and instrumentalsymptoms of intestinal damage, suggesting that they had ILC. Conclusions: The transient, stenosing and gangrenous forms of ischemic colitis, traditionally described in patients with CAI, rarely develop. Much more often, these patients can be found microscopic ischemic colitis